Global migration : the basics - Hanlon, Bernadette, 1969-; Vicino, Thomas J. (London ; New York, 2014)
"This book challenges students of geography, political science, public policy, sociology, and economics to look beyond the rhetoric and consider the real and basic facts about migration. Through detailed examinations of the scholarly literature, demographic patterns, and public policy debates, Global Migration: The Basics exposes readers to the underlying causes and consequences of migration"--
Includes bibliographical references and index.
Keywords: Human beings -- Migrations; Emigration and immigration; Human geography; SOCIAL SCIENCE / Human Geography; SOCIAL SCIENCE / Emigration & Immigration; SCIENCE / Earth Sciences / Geography